2012
DOI: 10.1029/2012jd017657
|View full text |Cite
|
Sign up to set email alerts
|

The initial stage processes of rocket‐and‐wire triggered lightning as observed by VHF interferometry

Abstract: [1] We examine VHF interferometric images, channel-base currents, and broadband electric field waveforms of the initial stage (IS) in two rocket-and-wire triggered lightning flashes. Two types of negative leaders, termed "long-duration" and "short-duration" leaders, were imaged by the VHF interferometers during the IS of the two flashes. There were three leaders that had relatively long durations of more than a few milliseconds. These three leaders were not accompanied by a significant change of channel-base c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 27 publications
(52 reference statements)
5
30
1
Order By: Relevance
“…[] (as introduced in section 4.1) is unreasonable. Here, combined with the observations by different authors [e.g., Shao et al ., ; Rakov et al ., ; Mazur and Ruhnke , ; Yoshida et al ., ], we agree with Winn et al . [] on the issue of the generation (or origin process) of M‐component.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…[] (as introduced in section 4.1) is unreasonable. Here, combined with the observations by different authors [e.g., Shao et al ., ; Rakov et al ., ; Mazur and Ruhnke , ; Yoshida et al ., ], we agree with Winn et al . [] on the issue of the generation (or origin process) of M‐component.…”
Section: Discussionsupporting
confidence: 93%
“…[] and by Yoshida et al . [] concerned such intercloud processes, and their descriptions of M breakdown and streamer (or leader) developments are useful for the further investigation of the M mechanism through the channel, which will be discussed in the following section.…”
Section: Mechanism Of M‐componentmentioning
confidence: 99%
See 1 more Smart Citation
“…Shao et al (), who used a narrowband very high frequency (VHF) interferometer, found that the initiation of M‐components was usually associated with the development of an in‐cloud channel making connection to the channel carrying continuing current (CC) to ground. Similar observations for initial continuous current (ICC) pulses and M‐components in rocket‐triggered lightning were reported by Yoshida et al () and Pilkey et al () from VHF imaging of lightning channels by a wideband VHF interferometer and a Lightning Mapping Array, respectively. An example of electric field signature of in‐cloud leader making connection with the continuing‐current‐carrying channel and producing a hook‐shaped signature characteristic of M‐component is found in Figure 3 of Rakov et al ().…”
Section: Introductionsupporting
confidence: 83%
“…Yoshida et al (), who analyzed wideband VHF interferometric images of the initial stage in two rocket‐triggered lightning flashes in conjunction with the corresponding channel‐base current records, observed that ICC pulses are initiated by either “short‐duration” or “long‐duration” leaders. The former, whose durations were about a few hundreds of microseconds, were inferred to be recoil leaders developing in remnants of previously formed channels, while the latter, which lasted more than a few milliseconds, appeared to be separate in‐cloud leaders developing in virgin air.…”
Section: Introductionmentioning
confidence: 99%